POLE and Mismatch Repair Status, Checkpoint Proteins and Tumor-Infiltrating Lymphocytes in Combination, and Tumor Differentiation: Identify Endometrial Cancers for Immunotherapy - Dong, Dandan; Lei, Huajiang; Liu, Duanya; Bai, Hansong; Yang, Yue; Tang, Baijie; Li, Ke; Liu, Juan; Xu, Gang; Xiao, Xue (Frontiers in Oncology, 2021)
Objective Although Polymerase-epsilon (POLE)-mutated and mismatch repair (MMR)-deficient endometrial cancers (ECs) are considered as promising candidates for anti-PD-1/PD-L1 therapy, selecting only these patients may exclude other patients who could potentially respond to this treatment strategy, highlighting the need of additional biomarkers for better patient selection. This study aims to evaluate potential predictive biomarkers for anti-PD-1/PD-L1 therapy in addition to POLE mutation (POLEm) and MMR deficiency (MMRd). Methods We performed next generation sequencing for POLE from 202 ECs, and immunohistochemistry for MLH1, MSH2, MSH6, PMS2, CD3, CD8, PD-1 and PD-L1 on full-section slides from these ECs. We assessed the association of POLEm and MMRd with clinicopathologic features, expression of check point proteins, and density of tumor-infiltrating lymphocytes (TILs). Prognostic impact of these immune markers was also evaluated. Results POLEm, MMRd and high-grade tumors exhibited elevated level of TILs. Increased expression of PD-1 and PD-L1 was observed in MMRd and high-grade ECs. A subgroup of MMR proficient ECs also harbored increased density of TILs, and positive expression of PD-1 and PD-L1. In addition, negative expression of checkpoint proteins and high density of TILs in combination was associated with good prognosis. Conclusions Candidates for PD-1 blockade may extend beyond POLEm and MMRd ECs, additional factors such as tumor grade, and combination of TILs levels and expression of checkpoint proteins may need to be considered for better patient selection.